KEMAMPUAN PEMERINTAH DALAM MENGEMBANGKAN POTENSI PARIWISATA (STUDI KASUS DI MANADO BEACH HOTEL DESA MOKUPA KECAMATAN TOMBARIRI KABUPATEN MINAHASA) - Michael Frederick; Femmy Tulusan; Joorie Ruru (JURNAL ADMINISTRASI PUBLIK, 2023)
ABSTRACT The purpose of this study is to find out the government's ability to develop tourism potential in Manado Beach Hotel, Mokupa Village, TombaririDistrict, Minahasa Regency. The method used in this study is descriptive using a qualitative approach.Qualitative descriptive research in this study is a method that aims to find the meaning behind the phenomenon can be done by associative study. For the results of this study, judging from the time factor, there are often delays in the process of providing services to the community. Judged from the skills of the government in terms of cooperation built by the government with the community in order to maintain cleanliness and environmental safety as well as with investors who will later participate in this development activity Furthermore, on knowledge from the government in the context of tourism development MBH (Manado Beach Hotel) has been well through the strategy taken by planning the establishment of regent regulations or also regional regulations so that it can be the basis for rebuilding MBH (Manado Beach Hotel) into a tourist destination in MokupaVillage. The advice from researchers is that the government continues to synergize and continue to maintain the cooperation that has been built both with fellow governments, with village governments, with the community and with investors, then the government must continue to be consistent with the plan for future regulatory determination programs so that later it can become the basis for the construction of MBH (Manado Beach Hotel). Keywords: Ability, Development, Tourism Potential